THE EFFECT OF COOPERATIVE LEARNING MODEL TYPE NUMBERED HEADS TOGETHER (NHT) BY USING VISUAL MEDIA OF CONCEPTUAL KNOWLEDGE PHYSICS STUDENTS - Fajar Kurniati; Prof. Sahyar (Universitas Negeri Medan, 2017)
This study aimed to determine the effect of cooperative learning model type Numbered Heads Together (NHT) by using visual media of conceptual knowledge students in topic dynamic electricity in class X SMA Swasta Mulia Pratama. Method of this research is by using quasi experiments with one group post test pretest design. Population in this research were all students in class X SMA Swasta Mulia Pratama. Sampling technique was total sampling that is class X-1 as experiment class using NHT and class X-2 as control class using direct insrtuctin model. The instrument used in this study there are test of learning outcomes in the form of essay 10 questions. Analysis using z-test. The results obtained average pretest experiments class was 9,57 and control class was 9,02 while average posttest experiments class was 50,97 and control class was 38,87. Average gain value of the experimental class value was 0,42 in sufficient category while control class was 0,32 in the low category. Hypothesis test results obtained zcount > ztable (3,75 > 1,65) so can be concluded that there is effect cooperative learning model type Numbered Heads Together (NHT) by using visual media on learning outcomes of conceptual knowledge